Development of a high thermal efficiency heavy-duty engine - Garcia, Erick; Triantopoulos, Vassilis; Trzaska, Joseph; Boehman, André L.; Taylor, Maxwell; Li, Jian (Frontiers in Thermal Engineering, 2025)
The U.S. Department of Energy Supertruck 2 program placed emphasis on development of heavy-duty trucks with high freight efficiency using commercially realizable technology suites. This paper describes the research and development process used to pursue a high thermal efficiency heavy-duty engine under Supertruck 2. The team focused on over-expanded engine cycles and advanced piston designs. This paper describes how single-cylinder engine studies using thermal barrier coated pistons, high compression pistons, and over-expanded cycles informed the development process of a multi-cylinder demonstration engine that achieved 49.9% peak thermal efficiency. While tailoring the injection strategy and other control parameters optimized the demonstration engine, more than half of the efficiency improvement came from the over-expanded cycle.